2012
DOI: 10.1200/jco.2011.41.4466
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydophila Psittaci Eradication With Doxycycline As First-Line Targeted Therapy for Ocular Adnexae Lymphoma: Final Results of an International Phase II Trial

Abstract: PurposeThe pathogenic association between Chlamydophila psittaci (Cp) and ocular adnexal marginal zone lymphoma (OAMZL) and the efficacy of doxycycline monotherapy have been investigated in retrospective series with variations in stage, management, and follow-up duration. To our knowledge, this is the first international phase II trial aimed at clarifying Cp prevalence and activity of first-line doxycycline in a homogeneous series of consecutive patients with newly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 25 publications
6
114
0
3
Order By: Relevance
“…8,9 Consequently, doxycycline treatment was studied as an initial therapeutic approach to POAML in several studies. [37][38][39] The overall response rate ranges from 45% to 65% in most studies 37,40 but was zero in a study reported by Grunberger et al 41 The 5-year For personal use only. on April 29, 2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Consequently, doxycycline treatment was studied as an initial therapeutic approach to POAML in several studies. [37][38][39] The overall response rate ranges from 45% to 65% in most studies 37,40 but was zero in a study reported by Grunberger et al 41 The 5-year For personal use only. on April 29, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…38,42 Information on C psittaci infection was reported in only 3 of the 9 studies. [38][39][40] Kim et al 40 reported equal responses in patients with C psittaci-positive and negative POAML, while 2 trials from Italy showed better responses in C psittaci-positive patients. 38,39 Only 1 of our patients received treatment with doxycycline with no response.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Helicobacter pylori (HP) has been studied in detail in these tumors and consequently antibiotic therapy is now the cornerstone of treatment. Microbial agents have been also implicated in other types of ENMZL: chlamydia psittaci in ocular adnexa, borrelia burgdorferi in skin, and campylobacter jejuni in small intestinal ENMZL [21][22][23]. ENMZL is also associated with long-standing autoimmune disorders involving the thyroid and salivary glands.…”
Section: Extranodal Marginal Zone Lymphoma (Enmzl)mentioning
confidence: 99%
“…Of note, MZL regression after doxycycline treatment has also been observed in some lymphomas with no C. psittaci presence as well as in cases in which this treatment failed to eradicate the C. psittaci infection (76,80,81). This finding suggests that other doxycycline-sensitive microorganisms may be linked with the lymphoma.…”
Section: Psittaci and Ocular Adnexal Mzlmentioning
confidence: 61%
“…A great deal of evidence supports a pathogenic association between C. psittaci and the development of MALT lymphoma of the ocular adnexa, ranging from the identification of chlamydial antigens in tumor tissue by immunohistochemistry and the detection of bacterial DNA in the tumor biopsies, to the visualization of the bacteria within tumor-infiltrating macrophages by electronic microscopy and their isolation from conjunctival swabs and the peripheral blood of patients (76,77). Moreover, development of metachronous C. psittaci-related lymphomas was described in the same patient after prolonged exposure to an infected animal (78).…”
Section: Psittaci and Ocular Adnexal Mzlmentioning
confidence: 99%